2019
DOI: 10.1182/bloodadvances.2019000293
|View full text |Cite
|
Sign up to set email alerts
|

Representation of therapy-related myelodysplastic syndrome in clinical trials over the past 20 years

Abstract: Key PointsPatients with t-MDS are underrepresented in clinical trials when taking into account the prevalence of such patients. Eligibility criteria and sponsorship type may contribute to t-MDS patient exclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…These are likely highly enriched for therapy‐related disease or may have had a very acute disease course that precluded trial participation; this is corroborated by the fact that the time to treatment was significantly longer for trial participants than nonparticipants. Only 10% of trial participants (in contrast to 24% of nonparticipants) had a diagnosis of therapy‐related MDS in our cohort, and this underscores the lack of trial provision for therapy‐related MDS 13 . Many clinical trials expressly exclude patients with a history of neoplasia, and this reflects how narrow trial eligibility criteria are a major issue in catering to this cohort of patients, who in fact have the greatest need for novel therapies 21 .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These are likely highly enriched for therapy‐related disease or may have had a very acute disease course that precluded trial participation; this is corroborated by the fact that the time to treatment was significantly longer for trial participants than nonparticipants. Only 10% of trial participants (in contrast to 24% of nonparticipants) had a diagnosis of therapy‐related MDS in our cohort, and this underscores the lack of trial provision for therapy‐related MDS 13 . Many clinical trials expressly exclude patients with a history of neoplasia, and this reflects how narrow trial eligibility criteria are a major issue in catering to this cohort of patients, who in fact have the greatest need for novel therapies 21 .…”
Section: Discussionmentioning
confidence: 84%
“…Only 10% of trial participants (in contrast to 24% of nonparticipants) had a diagnosis of therapy-related MDS in our cohort, and this underscores the lack of trial provision for therapy-related MDS. 13 Many clinical trials expressly exclude patients with a history of neoplasia, and this reflects how narrow trial eligibility criteria are a major issue in catering to this cohort of patients, who in fact have the greatest need for novel therapies. 21 This unmet need and the resultant required recruitment of patients with high-risk MDS into clinical trials upfront are exemplified by the fact that the survival benefit observed in the hallmark AZA-001 HMA trial has not been replicated in subsequent real-world studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, publications on t-MDS only are rare [21][22][23]. Not categorizing t-MDS as a subgroup of MDS limits proper clinical decision-making, interferes with epidemiological/ biological research, and supports the established practice of excluding t-MDS from clinical studies [24], thereby potentially preventing therapeutic improvements.…”
Section: Introductionmentioning
confidence: 99%